CRIMINAL PENALTY FOR FORCED CAPTURE OF COVID-19 BOARDS IN INDONESIA - Michelle Angelika S; Muhammad Ali Hanaafiah Selian (Yayasan Pendidikan Medika Indonesia, 2022)
Coronavirus is a virus that affects people all over the world and kills a lot of people. One of the social issues that develop is the community's compelled gathering of Covid-19's body without regard for safety and health procedures. This is hazardous since it has the potential to spread COVID-19.. This study examines numerous legal infractions resulting from the coercive collection of Covid-19 bodies, as well as several types of criminal liability in the collection of Covid-19 bodies.